PREPOSISI DALAM BAHASA INDONESIA: TINJAUAN BENTUK DAN PERAN SEMANTISNYA - Nusarini Nusarini (CARAKA, 2017)
This research entitled â€œPrepositions in Indonesian Language: Their Forms and Semantic Functionsâ€ aims to: (1) describe the forms of prepositions and (2) describe the semantic functions of prepositions in Indonesian language. This research belongs to descriptive research. The data were the sentences containing prepositions, while the sources of the data were Kompas newspaper, novel, Indonesian textbook and the researcher herself as the native speaker. The data collection techniques were the observation method covering uninvolved conversation observation technique and writing technique. The data analysis method used was distributional method covering the deletion technique and permutation technique, while the method of presenting the data analysis result was an informal method because the presentation involved words, not symbols. The results of the research are: (1) the forms of prepositions covered one-word or simple preposition and complex preposition. One-word preposition covers the base words and affixed words, while complex preposition covered adjoining preposition and correlated preposition, (2) prepositions have some semantic functions such as identifying the relation of primary semantics, direction, existence, members, tools, ways, aims, reasons, doers, equifinality, thing, comparison, time and condition.